Data from: Bionomics and insecticide resistance of the arboviral vector Aedes albopictus in northern Lao PDR ... - Tangena, Julie-Anne A.; Marcombe, Sebastien; Thammavong, Phoutmany; Chonephetsarath, Somsanith; Somphong, Boudsady; Sayteng, Kouxiong; Grandadam, Marc; Sutherland, Ian W.; Lindsay, Steve W.; Brey, Paul T. (Dryad, 2019)
In the last four decades there has been a staggering increase in the geographical range of the arboviral vector Aedes albopictus (Skuse, 1894). This species is now found in every continent except Antarctica, increasing the distribution of arboviral diseases such as dengue and chikungunya. In Lao PDR dengue epidemics occur regularly, with cases of chikungunya also reported. As treatment methods for arboviral diseases is limited, the control of the vector mosquitoes are essential. There is a paucity of information on the bionomics and resistance status of this mosquito for successful vector control efforts. Here we describe the bionomics and insecticide resistance status of Ae. albopictus in Laos to identify opportunities for control. Adult Ae. albopictus were collected using human-baited double bed net (HDN) traps in forests, villages and rubber plantations and tested for alpha- and flaviviruses with RT-PCR. Surveys were also conducted to identify larval habitats. Seven adult and larval populations ... : POne_Laos_Albo_bionomics_rawdata_IR_adultPOne_Laos_Albo_bionomics_rawdata_IR_larvaePOne_Laos_Albo_bionomics_rawdata_LarvalsurveyRaw data of the Ae. albopictus larval surveyPOne_Laos_Albo_bionomics_rawdata_AdultsurveyRaw data of the Ae. albopictus adult survey ...